Visual discourse in television (Al-Academy, 2024)
Visual discourse in cinema and television is an expressive medium that carries its audio and visual elements and is effective in influencing the memory of the recipient, according to multiple patterns of forms and representations aimed at persuasion, influence, entertainment, enjoyment and knowledge. This speech will not pass by the recipient without difficulty, as the multiplicity of forms and techniques of image presentation and the diversity of contents derived from different beliefs, concepts, ideas and perceptions may sometimes reach intersections and conflicts, which is reflected in the form of the screen and the theory of television. This motivates us to know the ways in which audio-visual discourse is produced on television, which constitutes a large and influential tributary in the space of Iraqi cultural discourse in our modern era.Within the topic of criticizing the Iraqi cultural discourse, visual discourse is evident as one of the tributaries of cultural discourse in its abundance of image artifacts, including techniques and kinetic treatments guided by aesthetic values and the perspective of the active signs in them, in patterns and approaches that constitute the world of image construction as a mediator of visual discourse. From this we find that television is an ongoing image station that faces the recipient around the clock to achieve communication with him through its visual speech. If we wanted to look, contemplate, and savor what is happening on this station in terms of visual sources, we would have referred to television criticism, as it is an evaluation of the television material shown in terms of its formal structure and its acquisition of the elements of the television formal language, in addition to the verbalized ideas, topics, and concepts it carries that reinforce this structure and help. On its evaluation, and what can be pointed out is the great technical development that has prevailed in the science of communication, with the multiplicity of efficiency of television production equipment and the emergence of many terrestrial and satellite television channels, which reveals a great openness with the viewer, which has increased the growth of experiences resulting from viewing, sorting, and discrimination to enhance the capabilities of television appreciation, which we believe A suitable ground or incubator for delivering the language of television criticism that targets the recipient in general